The Role of Justice in Achieving Long-term Buyer-Supplier Relationship: The Case of Jordanian Manufacturing Sector - Al-Ma'aitah, Noor (International Review of Management and Marketing, 2018)
The purpose of this paper is to investigate the role of justice in buyer-supplier relationships in the Jordanian manufacturing sector. Questionnaires were collected from 202 buyers in Jordan. Multiple regression results indicate that most of the research hypotheses were not supported (Distributive, Procedural, and Interpersonal), and only informational justice is supported. Based on these results, suppliers have to work with buyers to improve the perception of justice in order to build a long term buyer-supplier relationships. Opportunities for future empirical research are also identified. Keywords: Justice (fairness), Supply Chain Relationship, Jordan. JEL Classification: M1